Влияние структурных и технологических факторов на развитие собирательной рекристализации при спекании керамических материалов - Олейник, Г.С. (Вісник Українського матеріалознавчого товариства, 2013)
The findings on processes and mechanisms of collective recrystallization in ceramics (in particular based on oxides), including the author’s results of investigation into non-oxide ceramics, are generalized. The evolution of recrystallization is shown to be affected by both technological (temperature, techniques for sintering, rate of heating, presence of impurities et al.) and structural (plastic deformation, polymorphic transformations, formation and decomposition of solid solutions, effect of pores and inclusions of other phases located inside grains and on their boundaries) factors. It is suggested that the physical nature of the influence of these factors on the collective recrystallization is due to the change in the driving force of recrystallization and/or the mobility of intergrain boundaries.